Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Bagi Anak Tunadaksa Tingkat SMPLB - Hasani, Yaumul; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to determine how the implementation of physical education, sports and health for children with disabilities in SLB Negeri 1 Pagaruyung. This study used a qualitative descriptive method. Data collection used interview, observation, and documentation techniques. The data analysis technique was the results record of observations during the field, describe the problem and take conclusions. The results showed that during the process of implementing PJOK learning after the covid-19 pandemic was less than optimal due to a reduction time of learning activities. The strategy applied by PJOK teachers is a strategy and approach that is carried out directly, the method applied is the demonstration and drill method, the form of learning evaluation is direct improvements to students. The school provides a written modified curriculum for sports according to the implementation, students abilities and facilities and also infrastructure for learning according to the needs of the child.